1993
DOI: 10.1016/0266-7681(93)90014-7
|View full text |Cite
|
Sign up to set email alerts
|

Excision of the Hamate for an Unusual Hand Tumour

Abstract: A right-handed man with an enlarging bony swelling of his dominant hand developed symptoms of median and ulnar nerve compression. He underwent simple excision of the hamate and histology showed the lesion to be a benign chondroblastoma. At 2-year follow-up he was found to be doing a heavy manual job with no functional problems and there were no signs of recurrence of the tumour. To our knowledge this is the first reported case of a benign hand tumour treated by simple excision of the hamate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
0
8
0
2
Order By: Relevance
“…12 A review of the literature revealed only one reported case of a chondroblastoma involving the hamate that was treated with complete excision through a combined volar and dorsal approach. 4 Both cases of primary ABC involving the hamate were also treated with complete resection. 19,20 Although all 3 cases of hamate excision reported no carpal instability or decreased function, excision of the hamate might have important implications for finger and wrist biomechanics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 A review of the literature revealed only one reported case of a chondroblastoma involving the hamate that was treated with complete excision through a combined volar and dorsal approach. 4 Both cases of primary ABC involving the hamate were also treated with complete resection. 19,20 Although all 3 cases of hamate excision reported no carpal instability or decreased function, excision of the hamate might have important implications for finger and wrist biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…There has been only one reported case of chondroblastoma within the hamate. 4 The most common symptoms are pain, localized tenderness, and limitation of movement that usually is present for several months before the time of diagnosis. 12 Our patient presented with 6 months of wrist pain aggravated by ulnar deviation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Piramidal, semilunar y ganchoso también han sido asiento de este tumor. 3, 26,27 Como curiosidad, el trapecio apareció como afectado por un CB en 2008 por primera vez. 28 No se han reportado casos de afectación del trapezoide.…”
Section: Discussionunclassified
“…10 Curettage and bone graft is the preferred treatment for chondroblastoma in the hands or wrist. However, Daly et al 15 reported that chondroblastoma of the hamate was treated with complete excision. Although 1 treatment option is complete excision of the carpal bone, this approach seems to be overtreatment because chondroblastoma is believed to be less aggressive in the carpal bones.…”
Section: A B Cmentioning
confidence: 99%